2011
DOI: 10.1016/j.ajpath.2010.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Pterygium

Abstract: Pterygia are common ocular surface lesions thought to originate from limbal stem cells altered by chronic UV exposure. Traditionally regarded as a degenerative condition, pterygia also display tumor-like features, such as a propensity to invade normal tissue and high recurrence rates following resection, and may coexist with secondary premalignant lesions. This study was initiated to determine the rate of concurrent ocular surface diseases in patients with pterygia recruited from the practice of a single surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
133
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(140 citation statements)
references
References 62 publications
1
133
0
6
Order By: Relevance
“…A previous study also reported a decreased p63 expression in the more superficial cell layers of pterygium, with a staining pattern very similar to the normal sclerocorneal limbus [34]. In a recent study, Chui et al [35] observed in pterygia some morphologically primitive cells resembling limbal stem cells (LSCs) through their co-expression of cytokeratin (CK)-15, CK-19, and p63α. These cells appeared to be localized at the advancing head of the pterygium and they suggested that pterygium was a disease of LSCs, and the presence of these cell clusters may account for the clinical behavior of pterygium.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported a decreased p63 expression in the more superficial cell layers of pterygium, with a staining pattern very similar to the normal sclerocorneal limbus [34]. In a recent study, Chui et al [35] observed in pterygia some morphologically primitive cells resembling limbal stem cells (LSCs) through their co-expression of cytokeratin (CK)-15, CK-19, and p63α. These cells appeared to be localized at the advancing head of the pterygium and they suggested that pterygium was a disease of LSCs, and the presence of these cell clusters may account for the clinical behavior of pterygium.…”
Section: Discussionmentioning
confidence: 99%
“…(8) y Canadá (17) . Por el contrario, dos estudios realizados en Australia encontraron frecuencias no sospechada del 5 (16) y 9,8% (15) . Es probable que estas investigaciones australianas reportaran frecuencias más altas, porque el estudio histopatológico de los especímenes de pterigión se desarrolló específicamente para identificar la presencia de NESO.…”
Section: Discussionunclassified
“…Es probable que estas investigaciones australianas reportaran frecuencias más altas, porque el estudio histopatológico de los especímenes de pterigión se desarrolló específicamente para identificar la presencia de NESO. Otras razones que pueden explicar la mayor frecuencia en Australia incluyen un índice de radiación UV alto debido a la deficiencia de la capa de ozono en esta región (23,24) , la mayor susceptibilidad de la raza caucásica para desarrollar NESO que está relacionada a la piel blanca y/o iris pálido (23) y posiblemente a factores genéticos (8,(15)(16)(17)25) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…We showed here that basal cells had a higher VEGF mRNA amplification score compared with epithelial cells from the upper layers of the pterygium epithelium. High VEGF mRNA levels detected on the basal cells could be explained by their particular phenotype and behavior described by Chui et al [19], who suggested that basal cells could have a premalignant features. One of our previous studies concerning the presence and distribution of thymine dimers inside pterygium epithelium showed that basal cells are characterized by the highest expression of thymine dimers, which was also associated with a high density of p53 mutant basal cells [20].…”
Section: Discussionmentioning
confidence: 99%